Structural characteristics of camel-bone gelatin by demineralization and extraction - AL-Kahtani, HA; Jaswir, I; Ismail, EA; Ahmed, MA; Hammed, AM; Olorunnisola, S; Octavianti, F (TAYLOR & FRANCIS INC, 2024)
Camel bone was demineralized through HCl acidulation process at different concentrations (0.0%, 1.5%, 3.0%, and 6.0%) over 1-5 days. The level of demineralization was acid concentration and soaking time dependent. Highest demineralization (62.0%) was recorded in bone sample treated with 6.0% dilute acid for 5 days. Energy dispersive X-ray spectroscopy (EDX) elemental analysis revealed reduction in Ca and increase in N and H, while O remains unaffected. Particulate characteristics by scanning electron microscope showed an increased surface roughness of bone after demineralization. Fourier transform infrared (FT-IR) analysis of ossein depicted the presence of functional group similar to that of bone protein (collagen). Statistical optimization by central composite design (CCD) revealed a significant quadratic model for optimum values of extraction temperature, pH, and extraction time. The highest gelatin yield from camel bone was 23.66% at optimum extraction condition (71.87 degrees C, pH 5.26, and 2.58 h) and the bloom was 205.74 g. Camel bone is suitable for production of gelatin with good potentials in food and nonfood applications.